Folic acid supplement rescues ethanol-induced developmental defects in the zebrafish embryos. (5th May 2020) - Jiang, Qiu; Lu, Ding; Wang, Feng; Zhang, Yawen; Cao, Li; Gui, Yonghao; Sun, Shuna
Abstract: Fetal alcohol syndrome (FASD) describes a range of birth defects. Mechanisms of FASD-associated defects are not well understood. It has great significance to investigate whether nutrient supplements like folic acid (FA) can effectively rescue ethanol-induced defects. Moreover, it is very important to determine the optimal time for FA supplementation when it can most effectively antagonize the teratogenic effects of ethanol during embryonic development. Our results indicated that ethanol exposure interrupted the development of zebrafish embryos and induced multiple defects in cardiac function, pharyngeal arch arteries, vessel, craniofacial cartilage, pharyngeal arches, brain, somite and hemoglobin formation. The expressions of critical genes that play important roles in above organs such as tbx1, flk-1, hand2, ngn1, huc, titin, gata-1 and c-myb were reduced, and the apoptosis was increased in ethanol-treated group. FA supplementation could reverse ethanol-induced defects, improve the decreased expressions of above genes and reduce the apoptosis. We also found that giving FA at 6–12 h post-fertilization (hpf), which is at the gastrula period (5.25–10 hpf), can obviously prevent the teratogenicity of ethanol. This research provides clues for elucidating the mechanism of fetal abnormalities caused by alcohol intake and for preventing FASD.